Bioethics Medical, Ethical and Legal Perspectives - Clark, Peter A. (IntechOpen, 2016)
The main strength of this book is that it examines the challenges facing the field of Bioethics today from medical, ethical and legal perspectives. A critical exchange of ideas from professionals in interdisciplinary fields allows everyone to learn and benefit from the insights gained through others' experiences. Examining, analyzing and understanding these complex medical-ethical-legal issues and cases and how they are resolved will serve as a paradigm for all professionals who will be confronted with these complex bioethical issues now and in the future. The more we face these challenges directly, examine them critically and debate them enthusiastically the more knowledge will be gained and hopefully, we will gain more practical wisdom.